Indomethacin Induces Spermidine/Spermine-N1-Acetyltransferase-1 via the Nucleolin-CDK1 Axis and Synergizes with the Polyamine Oxidase Inhibitor Methoctramine in Lung Cancer Cells - Neudo Buelvas; Isidora Ugarte-Vio; Laura Asencio-Leal; Matías Muñoz-Uribe; Antonia Martin-Martin; Alejandro Rojas-Fernández; José A. Jara; Julio C. Tapia; María Elena Arias; Rodrigo A. López-Muñoz (Biomolecules, 2023)
Indomethacin is a non-selective NSAID used against pain and inflammation. Although cyclooxygenase (COX) inhibition is considered indomethacin’s primary action mechanism, COX-independent ways are associated with beneficial effects in cancer. In colon cancer cells, the activation of the peroxisome proliferator-activated receptor-γ (PPAR-γ) is related to the increase in spermidine/spermine-N1-acetyltransferase-1 (SSAT-1), a key enzyme for polyamine degradation, and related to cell cycle arrest. Indomethacin increases the SSAT-1 levels in lung cancer cells; however, the mechanism relying on the SSAT-1 increase is unclear. Thus, we asked for the influence of the PPAR-γ on the SSAT-1 expression in two lung cancer cell lines: H1299 and A549. We found that the inhibition of PPAR-γ with GW9662 did not revert the increase in SSAT-1 induced by indomethacin. Because the mRNA of SSAT-1 suffers a pre-translation retention step by nucleolin, a nucleolar protein, we explored the relationship between indomethacin and the upstream translation regulators of SSAT-1. We found that indomethacin decreases the nucleolin levels and the cyclin-dependent kinase 1 (CDK1) levels, which phosphorylates nucleolin in mitosis. Overexpression of nucleolin partially reverts the effect of indomethacin over cell viability and SSAT-1 levels. On the other hand, Casein Kinase, known for phosphorylating nucleolin during interphase, is not modified by indomethacin. SSAT-1 exerts its antiproliferative effect by acetylating polyamines, a process reverted by the polyamine oxidase (PAOX). Recently, methoctramine was described as the most specific inhibitor of PAOX. Thus, we asked if methoctramine could increase the effect of indomethacin. We found that, when combined, indomethacin and methoctramine have a synergistic effect against NSCLC cells in vitro. These results suggest that indomethacin increases the SSAT-1 levels by reducing the CDK1-nucleolin regulatory axis, and the PAOX inhibition with methoctramine could improve the antiproliferative effect of indomethacin.